Pregnancy and delivery after traumatic brain injury: a nationwide population-based cohort study in Finland. (12th December 2022) - Vaajala, Matias; Kuitunen, Ilari; Nyrhi, Lauri; Ponkilainen, Ville; Kekki, Maiju; Luoto, Teemu; Mattila, Ville M.
Abstract: Objectives: Few studies have assessed pregnancies and deliveries after traumatic brain injury (TBI). We report the incidence of TBIs and TBI-related surgeries in fertile-aged females and investigate subsequent pregnancy outcomes. Methods: All fertile-aged (15–49) women with TBI diagnosis during our study period (1998–2018) were retrieved from the Care Register for Health Care and combined with data from the National Medical Birth Register. TBIs were categorized into three subgroups based on the length of the hospitalization period and the need for neurosurgery. Logistic regression was used to analyze preterm deliveries, cesarean sections (CS) and neonatal health. Results are reported as adjusted odds ratios (AOR) with 95% confidence intervals (CI). Results: The incidence of TBIs increased from 103 per 100 000 person-years in 1998 to 257 per 100 000 (149.5%) in 2018. The incidence of TBI-related surgeries remained stable during our study period. The rate of preterm deliveries was 5.6% in the TBI group and 3.0% in the control group (AOR 1.23, CI 1.17–1.28). The CS rate in the TBI group was 19.2% and 15.9% in the control group (AOR 1.23, CI 1.18–1.29). The use of labor analgesia was higher among women with previous TBI. The rate of neonates requiring intensive care in the TBI group was 13.1% and 9.9% in the control group (AOR 1.30, CI 1.24–1.37). Conclusion: The incidence of TBI hospitalizations increased during our study period, whereas the number of surgically treated TBI remained stable. Preterm deliveries, CS, instrumental vaginal deliveries and labor analgesia were more prevalent in women with previous TBI. Furthermore, more neonates required intensive care in this group. Therefore, a history of TBI should be acknowledged as a possible factor affecting the delivery and health of the neonate.